Triumph of Moro diplomacy - Laarhoven, Ruurdje (Quezon City : New Day, 1989)
At head of title: The Maguindanaos Sultanate in the 17th century
Keywords: Maguindanao; Mindanao -- Foreign economic relations -- History; Mindanao -- History